Don't go [compact disc, unabridged] - Scottoline, Lisa (Macmillan Audio, 2013)
When Dr. Mike Scanlon is called to serve as an army doctor in Afghanistan, he's acutely aware of the dangers he'll face and the hardships it will bring his wife Chloe and newborn baby. And deep inside, he doesn't think of himself as a hero, but a healer.